Ductal adenocarcinoma of the prostate: A systematic review and meta‐analysis of incidence, presentation, prognosis, and management. Issue 1 (5th January 2021) - Ranasinha, Nithesh; Omer, Altan; Philippou, Yiannis; Harriss, Eli; Davies, Lucy; Chow, Ken; Chetta, Paolo M.; Erickson, Andrew; Rajakumar, Timothy; Mills, Ian G.; Bryant, Richard J.; Hamdy, Freddie C.; et al.
Abstract: Context: Ductal adenocarcinoma (DAC) is relatively rare, but is nonetheless the second most common subtype of prostate cancer. First described in 1967, opinion is still divided regarding its biology, prognosis, and outcome. Objectives: To systematically interrogate the literature to clarify the epidemiology, diagnosis, management, progression, and survival statistics of DAC. Materials and methods: We conducted a literature search of five medical databases from inception to May 04 2020 according to PRISMA criteria using search terms "prostate ductal adenocarcinoma" OR "endometriod adenocarcinoma of prostate" and variations of each. Results: Some 114 studies were eligible for inclusion, presenting 2 907 170 prostate cancer cases, of which 5911 were DAC. [Correction added on 16 January 2021 after the first online publication: the preceding statement has been corrected in this current version.] DAC accounts for 0.17% of prostate cancer on meta‐analysis (range 0.0837%‐13.4%). The majority of DAC cases were admixed with predominant acinar adenocarcinoma (AAC). Median Prostate Specific Antigen at diagnosis ranged from 4.2 to 9.6 ng/mL in the case series. DAC was more likely to present as T3 (RR1.71; 95%CI 1.53‐1.91) and T4 (RR7.56; 95%CI 5.19‐11.01) stages, with far higher likelihood of metastatic disease (RR4.62; 95%CI 3.84‐5.56; all P ‐values < .0001), compared to AAC. Common first treatments included surgery (radical prostatectomy (RP) or cystoprostatectomy for select cases) or radiotherapy (RT) for localized disease, and hormonal or chemo‐therapy for metastatic disease. Few studies compared RP and RT modalities, and those that did present mixed findings, although cancer‐specific survival rates seem worse after RP. Biochemical recurrence rates were increased with DAC compared to AAC. Additionally, DAC metastasized to unusual sites, including penile and peritoneal metastases. Where compared, all studies reported worse survival for DAC compared to AAC. Conclusion: When drawing conclusions about DAC it is important to note the heterogenous nature of the data. DAC is often diagnosed incidentally post‐treatment, perhaps due to lack of a single, universally applied histopathological definition. As such, DAC is likely underreported in clinical practice and the literature. Poorer prognosis and outcomes for DAC compared to AAC merit further research into genetic composition, evolution, diagnosis, and treatment of this surprisingly common prostate cancer sub‐type. Patient summary: Ductal prostate cancer is a rare but important form of prostate cancer. This review demonstrates that it tends to be more serious at detection and more likely to spread to unusual parts of the body. Overall survival is worse with this type of prostate cancer and urologists need to be aware of the presence of ductal prostate cancer to alter management decisions and follow‐up.